The Impact of Six-Dimensional (PDEODE) To Acquire the Literature Concepts by Eighth Graders in Kurdish Literature (Raparin Journal of Humanities (RJH), 2026)
The purpose of the this applied linguistic research is to find out the effectiveness and efficiency of the pedagogical strategy "six-dimensional" or named PDEODE in instruction of Kurdish literature for Eighth graders in order achieve a language acquisition. This study is conducted by designing examinations for two equal groups by the researchers. The experimental group is taught by the effectual strategy "six-dimensional", whereas the controlled group is educated by normal strategies and techniques. The evaluative exam was carried as a post-test. The participants are girls who are eighth graders from morning state schools of Duhok Educative directorate/ Ministry of education (KRG) in the academic year 2024-2025, their number is approximately 1935 students. Vina school for girls and Peshang schools were opted deliberately in the center of Duhok. The experimental group was selected randomly that contains 26 participants from Vina school, while the controlled group form from Peshang School which includes twenty-seven respondents. The evaluative exam was designed as form of MCQ which consists of three questions which is divided into twenty-four branches or sub questions. The assessment process was carried out from 2/10/2024 until 23/12/2024.T.test was adapted in order to assess and gain data for statistics. SPSS program is used to analyse data from the two collected samples. The experimental study shows the adaptation of six-dimensional strategy is very practical, useful, effective and efficient for acquiring literature concepts in contrast to the controlled group. The researcher found out the results, recommended and suggested the future research projects.